Navigating identities and building support community through art: A beyond-academia journey in Brussels - Stiti, Khaoula (Culture Caleidoscoop, 2024)
In this paper, I embark on a personal journey as an African woman and migrant researcher residing in Brussels, delving into the intersection of identity, academia, and solidarity. Beyond traditional academic confines, I navigate intricate power dynamics and uncover the significance of community and art. I acknowledge the challenges African researchers face in global academia, emphasising the need for solidarity and support within the academic community. Reflecting on my experiences as a researcher affiliated with an engineering institution, I discuss the reluctance in the engineering community to embrace decolonial methodologies and the tension between traditional academic expectations and unconventional approaches. Additionally, I delve into my identity as an African woman and migrant, highlighting challenges faced both in Tunisia and Brussels. This paper underscores the vital role of art and creative expression in fostering solidarity amongst marginalised communities and concludes by emphasising the importance of working from the margins to challenge power imbalances in academia and society.